Christology from Within: Exploring the Locus and Framework of a Socially Transformative Christology in Africa - Atansi, Chukwuemeka Anthony (Journal of reformed theology, 2024)
This article explores the place and framework for a socially transformative Christology, particularly in Africa. More specifically, it calls attention to the importance of grassroots christological imagination in the discussion of the social relevance of faith in Jesus Christ in Africa. The essay begins with highlighting the marginalization of the christological narratives of Christians at the grassroots still present in some of the academic discussions about the meaning and social significance of Christ in African Christianity. It then argues that taking seriously the grassroots Christologies, and a more critical-empathetic engagement of them within the framework of imagination and image, open up an effective way of doing Christology ‘from within’ the proclamation and longing of the People of God, who are graced to become both the embodiment and agents of Christ’s transforming presence and act. To this end, the article attempts to trace something of the mutual illumination connecting Christology and the transformation of society in Africa. And in doing so, it contributes to the task of bridging the gap that often exists between popular and academic Christologies.